2018
DOI: 10.3389/fimmu.2018.01519
|View full text |Cite|
|
Sign up to set email alerts
|

CD1d-Invariant Natural Killer T Cell-Based Cancer Immunotherapy: α-Galactosylceramide and Beyond

Abstract: CD1d-restricted invariant natural killer T (iNKT) cells are considered an attractive target for cancer immunotherapy. Upon their activation by glycolipid antigen and/or cytokines, iNKT cells can induce direct lysis of tumor cells but can also induce an antitumor immune response via their rapid production of proinflammatory cytokines that trigger the cytotoxic machinery of other components of the innate and adaptive immune system. Here, we provide an overview of various therapeutic approaches that have been eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…11,12 In most clinical studies DCs or PBMCs were loaded with α-GalCer ex-vivo before being administered into patients. 13 It was reported that intravenously (iv) injected cells led to a higher increase of iNKT cell numbers than intradermally (id) administered cells and the iv injected cells were only able to induce IFN-y production by T and NK cells. 14 However, in this study, id injected moDCs were unable to migrate to peripheral lymph nodes invalidating the comparison.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In most clinical studies DCs or PBMCs were loaded with α-GalCer ex-vivo before being administered into patients. 13 It was reported that intravenously (iv) injected cells led to a higher increase of iNKT cell numbers than intradermally (id) administered cells and the iv injected cells were only able to induce IFN-y production by T and NK cells. 14 However, in this study, id injected moDCs were unable to migrate to peripheral lymph nodes invalidating the comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, clinical studies have mainly focused on adoptive transfer of autologous iNKT cell enriched in vitro- expanded populations from peripheral blood mononuclear cells (PBMCs), αGalCer-pulsed monocyte-derived DCs or a combination of activated iNKT and αGalCer pulsed DCs ( 95 99 ). Also administration of soluble αGalCer has been tested in clinical trials ( 98 , 99 ). Currently, clinical benefits are still relatively limited and combinations as well as optimized strategies are being considered ( 96 , 99 ).…”
Section: Innate Lymphocyte Subsets In Natural and Therapeutic Anti-tumentioning
confidence: 99%
“…Also administration of soluble αGalCer has been tested in clinical trials ( 98 , 99 ). Currently, clinical benefits are still relatively limited and combinations as well as optimized strategies are being considered ( 96 , 99 ). Since ex vivo expansion of circulating iNKT has to overcome their low frequencies in blood, induced pluripotent stem cells (iPSCs) for the generation of large numbers of iNKT might provide an alternative ( 100 ).…”
Section: Innate Lymphocyte Subsets In Natural and Therapeutic Anti-tumentioning
confidence: 99%
See 1 more Smart Citation
“…We assess ILT cells within PBMC samples in this study, since previous studies have demonstrated ILT cell phenotypes in PBMC to be comparable with AT (14). As important first step toward therapeutic application, we also provide a differentiating analysis of MAIT, iNKT, and Vδ2 + T cell cytokine secretion upon general activation (i.e., combination of phorbol myristate acetate (PMA) and ionomycin) as well as stimulation using the MAIT agonist precursor 5-amino-6-D-ribitylaminouracil [5-A-RU (24)], and the iNKT and Vγ9 + Vδ2 + T cell agonists α-galactosylceramide [α-GC; used clinically by us and others (21,25)] and 4-bromo-3hydroxy-3-methylbutyl diphosphate [BrHPP; the only clinically tested phosphoantigen (26,27)], respectively.…”
Section: Introductionmentioning
confidence: 99%